Effect of Modified Male Infertox Treatment Plan in the Management of Oligoasthenozoospermia (Shukradushti) – Case Reports - Naram, Smita; Mahajan, Deepak; Parekh, Hemang (British Journal of Healthcare and Medical Research, 2022)
As per WHO a man is diagnosed with asthenozoospermia when there are less than 32% progressive motile sperm in the ejaculate and when sperm concentration is less than 15 million per milliliter of seminal sample is called oligozoospermia. This can lead to infertility in male as the path of the sperm must travel to fertilize the egg is too long and due to low motility and low count. Ayurveda describes seven dhatus, out of which Shukradhatu (reproductive tissue) included not only testicular tissue and ovarian tissue but also the stem cells present throughout the body. In Ayurveda Shukradhatu refers to testicular tissue and any abnormality in this can cause Beejdushti. As per Ayurvedic pharmacology the herbs are classified into two special groups Rasayana and Vajikarana, which aid the nourishment and stimulate the sexual tissues. Also there are few herbs classified into Shukrala which increase the spermatogenesis process. As per Acharya Kashyapa due to Virechana procedure sperms become active and motile and increases in number. In this present study the efficacy of Virechana (Detoxification) and Ayushakti Ayurveda made herbal remedies was assessed in the management of Shukrabeejdushti (Oligoasthenozoospermia).